2017
DOI: 10.2497/jjspm.64.338
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Damping Analysis of Cu-Sn/Carbon Fiber Sintered Composite Materials by Frequency Response Function of FFT Analyzer

Abstract: In recent years, in fields of an eco-friendly automobile, an advanced industrial machine, and a precision electronic device, controlling of vibration damping behavior of the sintered materials is required. In this paper, vibration damping analysis of Cu-Sn/Carbon fiber sintered composite materials was performed by frequency response function of FFT analyzer, and the results was compared with Cu-Sn/Graphite sintered composite materials.Cu, Sn elemental powders and Carbon fiber were used as initial substances. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Therefore, as the percentage of α-phase increases with increasing Sn content, the decay time shortens and the loss factor increases (Ogawa et al, 2019). However, the existence of a hard phase is considered to cause friction at the grain boundary with the matrix phase, and this friction converts the vibration energy into thermal energy, which dampens the vibrations (Ohzawa et al, 2017). In this study, the EDX and optical microscope observations showed that the test piece with 18.9% Sn content had a smaller percentage of α-phase compared to the test piece with 15.9% Sn content.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, as the percentage of α-phase increases with increasing Sn content, the decay time shortens and the loss factor increases (Ogawa et al, 2019). However, the existence of a hard phase is considered to cause friction at the grain boundary with the matrix phase, and this friction converts the vibration energy into thermal energy, which dampens the vibrations (Ohzawa et al, 2017). In this study, the EDX and optical microscope observations showed that the test piece with 18.9% Sn content had a smaller percentage of α-phase compared to the test piece with 15.9% Sn content.…”
Section: Resultsmentioning
confidence: 99%